Adverse Effects of Fillers and Their Histopathology - Haneke, Eckart (Facial Plastic Surgery, 2014)
Injectable fillers nowadays represent a pillar in facial rejuvenation and make a significant contribution to the success of the treatment. Despite their obvious benefits, a wide range of possible complications such as immediate, late, delayed, temporary, or irreversible adverse effects have to be respected. Differentiating the various filler materials, these effects are assigned to histopathology findings and currently available treatment options.
Keywords: adverse effect; filler; histopathology; complication management